Manajemen Ekonomi Outopilot: Kegagalan Negara Mencari Identitas? - Mukhaer Pakkanna (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2012)
Political democracy should be equivalent to the economic development of the quality of democracy, economic democracy if not upright, even the owner of the ruling power and money, which is parallel to force global corporatocracy. Consequently, the economic oligarchy preservation reinforces control of production and distribution from upstream to downstream and power monopoly of the market. The implication, increasingly sharp economic disparities, exclusive owner of the money and power become fertile, and the end could jeopardize the harmony of the national economy. The loss of national economic identity that makes people feel lost the “pilot of the state”. What happens then is the autopilot state. Viewing unclear direction of the economy, the national economy should clarify the true figure.